Management of Esophageal Foreign Bodies, retrospective study. - Nemat, Mohammed H.; Hussein, Abdulameer M.; Juma, Uday H. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Foreign body impaction in the esophagus is a common problem. Our Objective is to draw conclusions from a retrospective over viewing a number of cases to assess current methods of management and to come out with recommendation from collected experience.Patient and method: A retrospective study of (62) patients admitted to the Department of Thoracic and Cardiovascular Surgery at Medical City Teaching Hospital from January 2002 to December 2004 with history of foreign body swallowing and impaction. Six patients excluded from the (62) patients after having negative esophgoscpic findings. On presentation, history about type and time of ingestion, associated signs and symptoms were recorded, x- ray was taken. Rigid esophagoscopy or direct laryngoscopy and Magill forceps has been used. After the procedure completion, type and site of the foreign body and state of esophageal mucosa at the site of impaction were recorded. Chest Xray done postoperatively in certain patients when we had peroperative findings of bleeding, suspicion of perforation. All patients except 2 were discharged within 24 hours after the procedure.Results: The results showed that the commonest age group was among children between 1-10 years (27) patients, and 77% of the patients presented with dysphagia as the most common presenting symptom, site of impaction mostly in upper third of esophagus 68%, and 68% of the FB were radiopaque. Types of the FB were versatile but 50% of them were metalic objects.Conclusion: Esophageal FB is a common problem especially among children; it requires urgent intervention because of its deleterious complications if left untreated.Suspecion is enough indication especially in children. Management requires good experience in using the appropriate tools like Magill forceps, which is safe and quick in good hands.